Search for Mutations Connected With Non-Response to Anti-EGFR Therapy in mCRC in the Morphologically Defined Regions of Primary Tumours - Čarnogurská, Martina; Vasylieva, Valeriia Serhiivna; Macháčková, Táňa; Boudná, Marie; Pifková, Lucie; Orlíčková, Jana; Ivkovic, Tina Catela; Slabý, Ondrej; Bencsiková, Beatrix; Popovici, Vlad; Budinská, Eva (Cancer medicine, 2025)
BACKGROUND: Emerging evidence suggests that tumour morphological heterogeneity may influence mutational profiles relevant to therapy response. In this pilot study, we aimed to assess whether mutations identified within specific morphological patterns or at the invasion front correlate with shorter time to progression after anti-EGFR therapy, as compared to whole-tissue analysis. METHODS: We investigated genetic mutations in 142 samples from primary tumours of 39 KRAS wild-type metastatic colorectal cancer (CRC) patients receiving anti-EGFR therapy. Deep next-generation sequencing was performed on whole-tumour sections and six morphology-defined tumour regions. RESULTS: Mutations in genes linked to anti-EGFR therapy response (KRAS, BRAF, NRAS, PTEN and PI3KCA) were found uniquely in the non-responder group, with substantial variability across morphological sub-regions. BRAF mutations were aligned with serrated and mucinous morphologies, while KRAS mutations (p.Lys147Glu and p.Ala146Thr) were associated with mucinous and desmoplastic morphologies. In all cases, the cumulative mutational profile from sub-regions provided more details than that of the whole-tumour profile. CONCLUSION: Our findings highlight that comprehensive analysis, considering morphological heterogeneity, is crucial for personalised CRC treatment strategies.
Keywords: NRAS; protoonkogenní proteiny p21(ras); DNA Mutational Analysis; Male; kolorektální nádory; mutace; protinádorové látky; GTP-fosfohydrolasy; High-Throughput Nucleotide Sequencing; PTEN Phosphohydrolase; pilotní projekty; chemorezistence; Adult; invasion front; Aged; dospělí; GTP Phosphohydrolases; mužské pohlaví; senioři; metastatic cancer; inhibitory proteinkinas; mutační analýza DNA; PIK3CA; Proto-Oncogene Proteins B-raf; KRAS; senioři nad 80 let; tumour heterogeneity; lidé; ženské pohlaví; Humans; vysoce účinné nukleotidové sekvenování; Protein Kinase Inhibitors; erbB receptory; Aged, 80 and over; PTEN; Colorectal Neoplasms; Proto-Oncogene Proteins p21(ras); morphological sampling; Drug Resistance, Neoplasm; Mutation; fosfohydroláza PTEN; Pilot Projects; anti‐EGFR therapy; Female; protoonkogenní proteiny B-Raf; lidé středního věku; ErbB Receptors; BRAF; Antineoplastic Agents; Middle Aged